Risk factors and distribution features of level IB lymph nodes metastasis in nasopharyngeal carcinoma. Issue 3 (June 2019) - Zeng, Lei; Zhang, Qin; Ao, Fan; Jiang, Chun-Ling; Xiao, Yun; Xie, Hong-Hui; Tang, Yi-Qiang; Gong, Xiao-Chang; Li, Jin-Gao
Abstract: Objective: The objective of this study is to investigate the risk factors and distribution features for level IB metastasis in nasopharyngeal carcinoma (NPC) and provide clinical evidence for defining the indications and clinical target volume (CTV) of prophylactic level IB irradiation. Methods: We retrospectively analyzed 798 patients with newly-diagnosed, non-metastatic and histologically confirmed NPC underwent intensity-modulated radiation therapy (IMRT). Two sides of neck in each patient have been analyzed separately. The correlations of level IB metastasis and the clinical risk factors were analyzed with Chi-square test and logistic regression model. The risk score model (RSM) of level IB metastasis was calculated by totaling up the scores of each independent variable. We divided level IB into three areas, including anterolateral space of submandibular glands, medial space of the submandibular glands and submandibular glands. Results: Maximal axial diameter (MAD) of level IIA nodes >20 mm or extra capsular spread (ES) of level IIA nodes, anterior half of nasal cavity involvement and submandibular gland involvement/compression were independently significantly risk factors for level IB lymph nodes (LNs) metastasis at diagnosis. Two groups based on RSM were obtained: low risk (total score = 0–2.5); high risk (4–8.5). The incidence of IB LNs metastasis at diagnosis of the two groups were 0.9% and 6.3%, respectively (P < 0.001). The cervical lymph nodes of level IB were distributed in the anterolateral space of submandibular glands. There was no positive/negative LNs inside or medial space of the submandibular glands. Conclusion: Level IB LNs metastasis is associated with MAD of level IIA nodes >20 mm or ES of level IIA nodes, anterior half of nasal cavity involvement and submandibular gland involvement/compression in NPC patients. Omission of level IB irradiation may be feasible for patients with low-risk IB LNs metastasis at diagnosis. The submandibular gland should not be included in level IB.